Real Time Region-Based Umpire Pose Identification - Neeraj Varshney, Aekanshu Katyal, Ankit Sharma, Ashish Panigrahi, Ishan Kulshrestha, Sahil Vashishtha (International Journal of Control and Automation, 2020)
Technology has revolutionized the world. The infiltration of tech into our day-day activities has been gradual. Since Technology brings the potential for constant transformation in every corner of our lives, it has also kept its pace with the game of Cricket. With Spider-cams, speed guns, Decision Review System (DRS) came into the picture, both players and umpires are dependent on it some way or the other. The underlying idea of this paper is to detect umpire actions so that we canmaintain scoreboard efficiently. We introduced an idea of using Image filters to achieve the goal. Having detected the poses using structural elements of rectangular and elliptical shapes, the image is passed through various image filters. With the help of creating Flags (a signal to let the program to know that a certain condition has met) and based on active flags, weidentified actions namely: SIX, WIDE, OUT, NO BALL.This approach to detect Umpire actions is an effective solution for maintaining scorecard efficiently.